Efficacy of Extracorporeal Shock Wave Therapy for Achilles Tendinopathy: A Meta-analysis. Issue 2 (27th February 2020) - Fan, Yifei; Feng, Ziyan; Cao, Jun; Fu, Weili
Background: Achilles tendinopathy is a frequent sports injury, and extracorporeal shock wave therapy (ESWT) has been proposed as a treatment. Purpose: To compare outcomes between ESWT and other nonsurgical intervention (including sham shock wave therapy) in Achilles tendinopathy patients. Study Design: Systematic review; Level of evidence, 2. Methods: We included 5 randomized controlled trials and 3 case-control studies published between 2005 and 2018. We analyzed pain scores and other outcomes that were reported in more than 3 of the 8 studies. Results: ESWT was associated with significantly better scores than comparison therapy on the visual analog scale for pain ( P < .01), American Orthopaedic Foot & Ankle Society scale ( P = .01), Likert scale for satisfaction ( P = .03), Roles and Maudsley scale ( P < .01), Victorian Institute of Sports Assessment–Achilles questionnaire ( P < .01), and numerical rating scale ( P = .02). The 2 patient groups did not differ significantly in tenderness ( P = .34) or pain threshold ( P = .24). Subgroup analysis showed that ESWT led to better VAS pain scores than comparison treatments at both low-energy level (0.06-0.11 mJ/mm 2 ) and medium-energy level (0.12-0.25 mJ/mm 2 ) and at both shorter (<6 months) and longer (≥6 months) follow-up. Conclusion: ESWT improves pain and functional outcomes in patients with Achilles tendinopathy. Further research is needed to determine the optimal energy level.